Audit Sistem Enterprise Resources Planning â€œOracle Fusion Applicationâ€ menggunakan Framework COBIT 5 (Studi Kasus di FITB Institut Teknologi Bandung) - Sinaga, Frendy; Nugraha, Darya Setia (Indonesian Accounting Research Journal, 2024)
The establishment of Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions is the foundation for every company, state administrator, business entities, and the public to organizing, managing, and operating their activities. As well as the Bandung Institute of Technology, is supported and adopts the ERP System "Oracle Fusion Application" in its financial management and governance. However, in their implementation, there are still problems. The information system audit in this study uses the COBIT 5 framework with the IT Process in all EDM, APO, BAI, DSS, and MEA domains. The results showed that the maturity of the Oracle Fusion Application ERP System was 3.50, meaning that it was at level 3 with the category "Predictable Process" that means, the Faculty has implemented the governance process according to a predetermined process, but still refers to management framework whose relevance must be adjusted to the faculty